PRODUÇÃO E COMPOSIÇÃO QUÍMICA DO CAPIM ELEFANTE cv. PIONEIRO COLHIDO EM DIFERENTES ALTURAS DE RESÍDUO - Figueira, Danúbia Nogueira (2015)
The study was conducted at the Universidade Estadual do Centro Oeste, Guarapuava - PR, to evaluate the dynamics of production and chemical composition of elephant grass cv Pioneiro fodder, managed at different times of residue 30, 40, 50 and 60 cm, associated with the harvest dates, in two consecutive years. The experimental design was a randomized block in time split plot, with the plots with four residues were, and the subplots three harvest seasons. In the year of implementation, significant interaction between time of residue and harvest time for participation of stem and leaf in the physical structure of forage, fresh biomass production and production of dry matter. There was a quadratic effect on dry biomass production for all harvest times, with the point of maximum production of 5.738 kg ha?¹ up to residue of 50.17 cm for the second harvest season, where it was estimated maximum production potential. On the average, the increase in elephant grass residue in height from 30 to 60 cm, regardless of the harvest season, promoted reduction in NDF and ADF forage, with consequent increase in crude protein. For the second year of evaluation, a significant interaction between time of residue and harvest time for crude protein of stem and sheath, and fiber in neutral detergent sheet. There was no statistical difference for dry matter production in different heights residue, with each average cut of 1.842 kg ha?¹. There was no statistical difference between waste of time to crude protein content of leaf and forage with averages of 15.65% and 12.50%, respectively. For neutral detergent fiber and acid, forage showed an average of 66.19% and 42.66%, respectively. Considering the balance between production and quality, the waste of time recommended for the management of elephant grass foraging at different times of crop is 40-50 cm.